The effect of foreign equity ownership on corporate social responsibility: Empirical evidence from Poland - Anna Doś (e-Finanse: Financial Internet Quarterly, 2017)
In the literature on corporate social responsibility (CSR) the origin of the equity is seen as one the drivers of CSR. There is evidence of multinational corporations stimulating diffusion of CSR practices in a few emerging economies. There are no similar studies focusing on the Polish economy. Since CSR practices are country-specific it is important to investigate if and how capital flows foster corporate social responsibility among firms established and operating in Poland. The method applied in the study is a statistical analysis of the ownership structure of firm whose socially responsible practices are highly ranked by the independent think-tanks compared to the ownership structure of their most relevant competitors. The results allow for a more comprehensive understanding of CSR drivers in Poland as well as the role of foreign capital in reshaping economic structures in Poland.
Keywords: G32; M14; A130; 330; ownership structure; multinational enterprises; transition